Prokaryotic and eukaryotic skin microbiota modifications triggered by Leishmania infection in localized Cutaneous Leishmaniasis. - Jesús Jaimes; Luz Helena Patiño; Giovanny Herrera; Claudia Cruz; Julie Pérez; Camilo A Correa-Cárdenas; Marina Muñoz; Juan David Ramírez (Public Library of Science (PLoS), 2024)
Cutaneous Leishmaniasis (CL) is a tropical disease characterized by cutaneous ulcers, sometimes with satellite lesions and nodular lymphangitis. Leishmania parasites, transmitted by sandfly vectors, cause this widespread public health challenge affecting millions worldwide. CL's complexity stems from diverse Leishmania species and intricate host interactions. Therefore, this study aims to shed light on the spatial-temporal distribution of Leishmania species and exploring the influence of skin microbiota on disease progression. We analyzed 40 samples from CL patients at three military bases across Colombia. Using Oxford Nanopore's Heat Shock Protein 70 sequencing, we identified Leishmania species and profiled microbiota in CL lesions and corresponding healthy limbs. Illumina sequencing of 16S-rRNA and 18S-rRNA genes helped analyze prokaryotic and eukaryotic communities. Our research uncovered a spatial-temporal overlap between regions of high CL incidence and our sampling locations, indicating the coexistence of various Leishmania species. L. naiffi emerged as a noteworthy discovery. In addition, our study delved into the changes in skin microbiota associated with CL lesions sampled by scraping compared with healthy skin sampled by brushing of upper and lower limbs. We observed alterations in microbial diversity, both in prokaryotic and eukaryotic communities, within the lesioned areas, signifying the potential role of microbiota in CL pathogenesis. The significant increase in specific bacterial families, such as Staphylococcaceae and Streptococcaceae, within CL lesions indicates their contribution to local inflammation. In essence, our study contributes to the ongoing research into CL, highlighting the need for a multifaceted approach to decipher the intricate interactions between Leishmaniasis and the skin microbiota.